Ultrasound of the Athletic Groin - Campbell, Rob (Seminars in Musculoskeletal Radiology, 2013)
Athletic groin pain may be the result of a wide variety of different pathologic processes. Clinical diagnosis may be difficult, and imaging can play a vital role in diagnosis. Magnetic resonance imaging is frequently used as the primary imaging modality. However, ultrasound is the best image modality for dynamic assessment of soft tissue abnormality and for guided intervention. Ultrasound (US) is often used as a problem-solving tool. This article briefly reviews the specific roles for US in management of groin pain in the athlete.
Keywords: ultrasound; groin; pubalgia; hernia; muscle; injury